The Influence of Television Access and Impersonating Violent Contents to Bullying Behavior on Elementary School Children - Nunky Ajeng Arifinda; Dwi Hastuti (Department of Family and Consumer Sciences, Bogor Agricultural University, 2016)
Television programs containing violence is now free to be accessed by school age children, particularly children in elementary school. The violent content has negative impact on children, such as bullying behavior to their friends as well as their parents. This research aimed to analyze the influence of television access on bullying behavior among school age children at Bogor villages. This research involved 60 children with age ranges between 10-13 years old in grade 4 and 5. A proportional random sampling in Pamijahan Sub-District, Bogor District was undertaken in this research. Result showed that the intensity of watching television, preferences in watching television, preferences to access violent contents, and impersonation of violent contents significantly correlated to bullying behavior. Multiple linier regression analysis showed that television access and impersonating violent contents had significantly positive effects on bullying behavior on children. Keywords: bullying behavior, elementary school children, impersonating violent contents, rural area, television access Tayangan televisi yang banyak mengandung kekerasan dapat secara bebas diakses oleh anak usia sekolah. Akibatnya, anak dapat berulang-ulang terpapar muatan kekerasan tersebut dan berpotensi meniru adegan kekerasan tersebut dan melakukan perilaku bullying terhadap teman-teman bahkan orangtuanya. Penelitian ini bertujuan untuk menganalisis pengaruh akses media televisi terhadap perilaku bullying anak usia sekolah di Perdesaan Bogor. Penelitian ini melibatkan 60 anak usia sekolah berusia 10-13 tahun yang duduk di kelas 4 dan 5 SD yang dipilih secara proportional random sampling. Penelitian ini berlokasi di Kecamatan Pamijahan, Kabupaten Bogor. Hasil analisis menunjukkan bahwa lama menonton televisi, preferensi menonton televisi, preferensi mengakses muatan kekerasan, dan peniruan muatan kekerasan berhubungan positif signifikan dengan perilaku bullying. Uji regresi linier berganda menunjukkan bahwa akses media televisi dan peniruan muatan kekerasan berpengaruh positif signifikan terhadap perilaku bullying anak usia sekolah.Kata kunci: akses media televisi, peniruan muatan kekerasan, perdesaan, perilaku bullying, siswa sekolah dasar